2010
DOI: 10.1182/blood-2010-05-283309
|View full text |Cite
|
Sign up to set email alerts
|

The B-cell tumor–associated antigen ROR1 can be targeted with T cells modified to express a ROR1-specific chimeric antigen receptor

Abstract: Monoclonal antibodies and T cells modi- IntroductionB-cell chronic lymphocytic leukemia (B-CLL) and mantle cell lymphoma (MCL) are common B-cell malignancies that respond to chemotherapy but are rarely cured. Allogeneic hematopoietic stem cell transplantation (HCT) enables a T cell-mediated graft-versus-leukemia (GVL) effect and induces durable remissions in a subset of patients with chemotherapy-refractory B-CLL and MCL, demonstrating that these malignancies are susceptible to recognition and elimination by T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
220
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 225 publications
(234 citation statements)
references
References 36 publications
8
220
0
Order By: Relevance
“…3,4 In agreement with these studies, we identified the HLA-B*07:02-restricted ROR1 peptide NPRYPNYMF as a component of the HLA ligandome of CLL samples (Figure 1 A,B and Online Supplementary Table S1). In contrast, the ROR1 peptide could not be found in the HLA ligandome of normal cells (data not shown).…”
supporting
confidence: 67%
See 2 more Smart Citations
“…3,4 In agreement with these studies, we identified the HLA-B*07:02-restricted ROR1 peptide NPRYPNYMF as a component of the HLA ligandome of CLL samples (Figure 1 A,B and Online Supplementary Table S1). In contrast, the ROR1 peptide could not be found in the HLA ligandome of normal cells (data not shown).…”
supporting
confidence: 67%
“…It has been demonstrated that ROR1 messenger Ribonucleic Acid (mRNA) is highly expressed in CLL cells (Online Supplementary Figure S1) and a uniform expression of ROR1 protein is detected on their cell surface. 3,4 In contrast, ROR1 expression was not found in other blood cells or on bone marrow-derived cells, except on a small subset of precursor B cells.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Multiple cell surface antigens expressed by B cell malignancies, including CD19, CD20, CD22, CD23, CD38, ROR1, and kappa light chain, have been targeted with T cells engineered to express scFv-containing CAR constructs [13,15,[20][21][22][23][24][25], and some of these antigens are now being targeted in phase I clinical trials of CAR-modified T cell therapy (Table 1). Although targeting using a scFv incorporated into a CAR has remained the most prevalent strategy to target B cell malignancies, other approaches have been used to target CAR-modified T cells to solid tumors, for example by incorporation of IL-13 into a CAR to redirect engineered T cells to IL-13Ra2-expressing tumors [26].…”
Section: Design Of Chimeric Antigen Receptorsmentioning
confidence: 99%
“…Then, a drop of cell suspension was placed on a poly-L-lysine-coated glass slide , these experiments indicate that Raji cells express ROR1. ROR1 is the receptor tyrosine kinase-like orphan receptor 1 and functional data suggest that ROR1 may act in Wnt-signaling and promote the survival of malignant cells [49,50]. Raji cell line is from a Burkitt's lymphoma patient, which is a subtype of B-cell NHL.…”
Section: Force Spectroscopy Of Molecular Interactions On Tumor Cells mentioning
confidence: 99%